Implementation of Social Inclusion-Based Library Transformation Policies - Tri Haryanto; Edy Sutrisno; Mala Sondang Silitonga (International Journal of Economics Development Research (IJEDR), 2024)
The Social Inclusion-Based Library Transformation (SIBLT) program aims to increase literacy in realizing community welfare, but increasing literacy in The Special Region of Yogyakarta is not followed by an increase in community welfare. To analyse the determinant factors that cause high levels of literacy but low levels of community welfare, the researcher used a policy implementation model with the Van Meter and Van Horn model by adding the variables of technology use and community participation within the framework of qualitative research method with a case study approach in Kulon Progo regency and Sleman regency, DIY. As for the research results obtained, there are several determinant factors that influence the implementation of SIBLTin the two districts above, including policy standards and targets, organizational resources, inter-organizational community and activity measurement, characteristics of the implementating bureaucracy, socio-economic and political conditions, use of technology and community participation, attitude of implementers and policy performance. So that the implementation of SIBLT is in line with policy direction and objectives, strategies that can be used include increasing leadership commitment, drafting regulations, forming a coordination team, implementation National Action Plan (NAP) and Regional Action Plan (RAP) as well as regular evaluation and monitoring.